2018
DOI: 10.1037/sgd0000267
|View full text |Cite
|
Sign up to set email alerts
|

Envisioning future parenthood among bisexual, lesbian, and heterosexual women.

Abstract: For many individuals, becoming a parent is an important milestone. The current study examined attitudes and beliefs about parenting among a sample of 196 self-identified bisexual, lesbian, and heterosexual women. Results showed no differences by sexual orientation for women's desires and intentions to have children, their idealization of parenthood, and perceptions of their parental self-efficacy (i.e., their ability to care for a child). In contrast, differences did emerge by sexual orientation in aspects suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
38
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 42 publications
5
38
2
Order By: Relevance
“…As for bisexual persons, previous studies have indicated more similarities in their attitudes to heterosexuals than to lesbians and gay men (Riskind and Tornello 2017). However, Simon et al (2018) recently found no differences concerning parenting desires and intentions among lesbians, bisexuals and heterosexual women.…”
Section: Impact Of Sexual Identity On Attitudes Toward Parenthoodmentioning
confidence: 91%
“…As for bisexual persons, previous studies have indicated more similarities in their attitudes to heterosexuals than to lesbians and gay men (Riskind and Tornello 2017). However, Simon et al (2018) recently found no differences concerning parenting desires and intentions among lesbians, bisexuals and heterosexual women.…”
Section: Impact Of Sexual Identity On Attitudes Toward Parenthoodmentioning
confidence: 91%
“…Having a job and a source of income are usually seen as instrumental precursors to having children (Umberson et al, 2010). As mentioned before, these aspects may be particularly relevant to sexual minority individuals' parenthood decisions, given the costs associated to adoption and assisted reproduction (Mezey, 2008;Downing et al, 2009;Goldberg et al, 2012;Riskind et al, 2013;Blanchfield and Patterson, 2015;Simon et al, 2018;Tate et al, 2019). In this regard, Simon et al (2018) found that, compared to their heterosexual and bisexual peers, lesbian women were more likely to want a permanent professional position before having children.…”
Section: Professional and Educational Statusmentioning
confidence: 95%
“…Regarding financial aspects, during the last decade high youth unemployment rates and the precariousness of existing jobs have led to financial instability and to the postponement of family projects by Portuguese young adults (Oliveira et al, 2014;PORDATA, 2019a). In the case of sexual minority persons, both the stigma and costs associated with adoption and assisted reproduction (Mezey, 2008;Downing et al, 2009;Goldberg et al, 2012;Riskind et al, 2013;Blanchfield and Patterson, 2015;Simon et al, 2018;Tate et al, 2019) make entry into parenthood a more costly social and economic undertaking than for heterosexual persons (Riskind et al, 2013;Blanchfield and Patterson, 2015;Simon et al, 2018;Tate et al, 2019). In fact, Tate and Patterson (2019b) found that lesbian women perceived parenthood as having a considerable cost and that this alone largely accounted for differences in parenthood aspirations between them and their heterosexual counterparts.…”
Section: Financial Emotional and Physical Costsmentioning
confidence: 99%
See 2 more Smart Citations